2020
DOI: 10.1097/sla.0000000000003633
|View full text |Cite
|
Sign up to set email alerts
|

The 100 Most Cited Papers in the History of the American Surgical Association

Abstract: Objective: The aim of this study was to determine characteristics of the most cited publications in the history of the American Surgical Association (ASA). Summary Background Data: The Annals of Surgery has served as the journal of record for the ASA since 1928, with a special issue each year dedicated to papers presented before the ASA Annual Meeting. Methods: The top 100 most cited ASA publications in the … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
11
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 13 publications
(11 citation statements)
references
References 33 publications
0
11
0
Order By: Relevance
“…Such studies have been conducted in many different surgical and non-surgical domains; however, none have been performed on COVID-19 related publications. 5 - 8 With respect to the COVID-19 pandemic, previous bibliometric analyses have been conducted to investigate research activity in different counties. 9 - 12 However, none were conducted with the goal of highlighting the most highly cited COVID-19 early research publications.…”
Section: Introductionmentioning
confidence: 99%
“…Such studies have been conducted in many different surgical and non-surgical domains; however, none have been performed on COVID-19 related publications. 5 - 8 With respect to the COVID-19 pandemic, previous bibliometric analyses have been conducted to investigate research activity in different counties. 9 - 12 However, none were conducted with the goal of highlighting the most highly cited COVID-19 early research publications.…”
Section: Introductionmentioning
confidence: 99%
“…The publication and citation counts can be influenced by the selection of databases, search strategy, and personal bias. A previous bibliometric analysis found that the Web of Science and Scopus exported very similar articles but different citations ( 18 ). Besides, the number of citations can be influenced by literature age, some newly published articles had low citations despite their high scientific values.…”
Section: Discussionmentioning
confidence: 99%
“…This article describes a citation analysis of journal articles in the field of psychooncology pertaining to the guidance of clinical practice and research. A review of the 100 most-cited papers is consistent with the methodological approach to bibliometric reviews in health research [13,14,16,17,[30][31][32][33]. A review protocol was developed to support the study's objectives, search strategy, inclusion/exclusion criteria and risk of bias assessment.…”
Section: Methodsmentioning
confidence: 99%
“…Furthermore, several key psychosocial-oncology journals are indexed within Scopus. Inclusion of one electronic database is standard practice in bibliometric analyses [14,16,17,30,31,33]. Results retrieved from Scopus were sorted using the sorting option "times cited-highest to lowest."…”
Section: Search Strategy and Study Selectionmentioning
confidence: 99%
See 1 more Smart Citation